Juana de Arco - Besson, Luc; Birkin, Andrew; Cassel, Vincent, 1966-; Dunaway, Faye; Greggory, Pascal, 1955-; Harrington, Desmond, 1976-; Hoffman, Dustin, 1937-; Jovovich, Milla; Karyo, Tchéky, 1953-; Malkovich, John; Ridings, Richard; Serra, Eric; et al. (Columbia Tristar Home Video, 2000)
Una joven mujer recibe la visión que ella conduciría y libraría a Francia de los opresores ingleses.